2018
DOI: 10.1080/02643294.2018.1457017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mirror-touch synaesthesia and empathy: New evidence and a new screening tool

Abstract: People with mirror-touch synaesthesia (MTS) report tactile sensations on their own body when seeing another person being touched. Although this has been associated with heightened empathy and emotion perception, this finding has been disputed. Here, we conduct two experiments to explore this relationship further. In Experiment 1, we develop a new screening measure for MTS. We show that MTS is related to vicarious experiences more generally, but is not a simple exaggerated version of normality. For example, peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(155 citation statements)
references
References 40 publications
(77 reference statements)
16
109
3
Order By: Relevance
“…Several studies do report on the relation between mirror-sensory synesthesia and social skills. Banissy et al [20] and Ward et al [19] showed that mirror-sensory synesthetes are better at judging subtle facial expressions, but not at recognition of faces, consistent with the idea that enhanced mirror-abilities in the somatosensory system can improve social perception through simulation. In another study by Baron-Cohen et al [28] however, synesthetes did not perform better on the Reading the Mind in the Eyes test, an assessment of 'theory of mind' abilities and social understanding [42], and they scored lower on the Social Skills component of the Empathy Quotient.…”
Section: Empathy Theory Of Mind and Altruism In Mirror-sensory Synementioning
confidence: 68%
See 3 more Smart Citations
“…Several studies do report on the relation between mirror-sensory synesthesia and social skills. Banissy et al [20] and Ward et al [19] showed that mirror-sensory synesthetes are better at judging subtle facial expressions, but not at recognition of faces, consistent with the idea that enhanced mirror-abilities in the somatosensory system can improve social perception through simulation. In another study by Baron-Cohen et al [28] however, synesthetes did not perform better on the Reading the Mind in the Eyes test, an assessment of 'theory of mind' abilities and social understanding [42], and they scored lower on the Social Skills component of the Empathy Quotient.…”
Section: Empathy Theory Of Mind and Altruism In Mirror-sensory Synementioning
confidence: 68%
“…Enhanced responses in the tactile mirror-system in non-synesthetes have been related to enhanced empathy ratings [5,17], suggesting that the more sensitive the tactile mirror system is, the more empathic individuals are. It is therefore not surprising that mirror-sensory synesthesia is related to enhanced empathy [1,18,19]. Because of enhanced socio-cognitive abilities [20], atypical self-other representations have also been proposed as the main mechanism of mirror-sensory synesthesia [21,22], with more inclusive representations of the 'self' facilitating the incorporation of others' experiences into their own body [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess MTS, participants filled out a screening questionnaire. Two participants had a score >7 (they scored 10 and 12), which Ward et al [51] suggest is a potential indication of MTS.…”
Section: Questionnaires (Planned Exploratory Research)mentioning
confidence: 90%